The financial effects of inflation - Cagan, Phillip; Lipsey, Robert E.; National Bureau of Economic Research (Cambridge, Mass. : Published for the National Bureau of Economic Research by Ballinger Pub. Co., 1978)
The book draws together the main results of the National Bureau's study and other works on the financial effects of inflation , to summarize what has been learned and what questions remain open
index.
Includes bibliographical references : p. 79-82.
osc 22/02/17
Loans
Keywords: Inflation (Finance); Finance; United States